The Effect of Price, Product Quality, and Advertising on Shoe Purchase Decisions at Al-Shoes Air Tiris Kampar Store - Ramadiah, Vivien; Syahdanur , Syahdanur (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study investigates how price, product quality, and promotion impact consumer decisions to purchase shoes at Al-Shoes Air Tiris Kampar Store. This study uses a quantitative approach, and data are collected through questionnaires distributed to participants. In this study, the sample and population consisted of 80 Air Tiris shoe buyers at Al-Shoes store. Sampling was carried out using the non-probability sampling method and the Slovin formula. Primary data were collected directly from respondents through questionnaires distributed to Air Tiris shoe buyers at Al-Shoes store. The results of the t-test show that, with a significance level of ? = 0.05, consumer decisions to purchase AL-Shoes brand Air Tiris footwear at the store are significantly influenced by each variable. The results show that t-count for the price variable is 1.211, the product quality variable is 3.611, and the promotion variable is 0.2199.